2014
DOI: 10.1371/journal.pone.0108412
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Periodontal Treatment on Hemoglobin A1c Levels of Diabetic Patients: A Systematic Review and Meta-Analysis

Abstract: BackgroundThere is growing evidence that periodontal treatment may affect glycemic control in diabetic patients. And several systematic reviews have been conducted to assess the effect of periodontal treatment on diabetes outcomes. Researches of this aspect are widely concerned, and several new controlled trials have been published. The aim of this study was to update the account for recent findings.MethodsA literature search (until the end of January 2014) was carried out using various databases with language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 50 publications
(145 reference statements)
2
58
1
1
Order By: Relevance
“…Eight SRs included randomized controlled trials (RCTs) only, and three SRs RCTs and controlled clinical trials. Most RCTs included in the SRs presented at least one of the domains assessed with unclear or high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Eight SRs included randomized controlled trials (RCTs) only, and three SRs RCTs and controlled clinical trials. Most RCTs included in the SRs presented at least one of the domains assessed with unclear or high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent meta-analyses have suggested that this conclusion must be interpreted with care due to the limited robustness and heterogeneity of the studies available in the literature [27,28].…”
Section: Biomedical Research 2018; 29 (3): 633-639mentioning
confidence: 99%
“…12 The guideline promoted education of diabetic patients by providers on oral hygiene and awareness of xerostomia risk (dry mouth). Both the 2013 consensus report of the Joint European Federation for Periodontology and American Academy of Periodontology Dental-Medical care delivery in T2DM workshop on periodontitis and systemic diseases 13 and metaanalysis of the impact of periodontal treatment on hemoglobin A1c levels (HbA1C), 14 concluded that guideline provision surrounding periodontal care in diabetic patients was supportable and associated with efficacy, and was further supported by meta-analysis of level A clinical trial evidence demonstrating moderate reduction in HbA1c and inflammatory biomarker levels and improvement in oral indices post intervention. 15 The American Academy of Oral Medicine also advanced evidence-based CPGs that include recommendations for optimizing clinical interventions to reduce risk of PD, caries, and oral infection in patients with Glurich, Nycz, Acharya Characterize current practice patterns for integrating dental practitioners into the medical home model.…”
Section: Current Interdisciplinary Practice Patterns: Does Oral Healtmentioning
confidence: 99%